Communicative effects of health visual messages on cigarettes packaging towards smokers / Rusydi Mohamad Kamal...[et.al] - Mohamad Kamal, Rusydi; Abdullah, Muhammad Hakimi Tew; Ridzuan, Abdul Rauf; Jafri, Fakrulnizam; Jaapar, Iqbal (Faculty of Communication & Media Studies, 2018)
This study on communicative effects of health visual messages on cigarettes packaging towards smokers is aimed at identifying the functions of visual communication of health message towards smokers on the danger of smoking. The new and aggressive strategy of displaying chronic diseases images on cigarettes packaging is chosen as the fundamental of this study as the researcher's intent to discover the effectiveness of the messages through visual communication in the form of health message. A qualitative approach with focused group interviews consisted of 10 informants from different demographic factors were done. Finding analysis is matched with the paradigm framework of active message processing written by Pfau and Parrot (1993) in the book entitled Persuasive Communication Campaigns which stated the stages of message processing by public and it is a useful model in research on the effectiveness of health messages. This study found that the messages have affected the informants' emotions in terms of creating fear but it does not work on giving permanent awareness thus they choose to reject the messages delivered on cigarettes packaging. As a conclusion, the displaying of visual messages has given a shortterm effect but eventually it becomes a norm and not getting bothered by the message receivers. However, there are also consequences of directly displaying the visual messages to the receivers since it is an act of informing that affects emotions.